Asia and the Holy See - Ueno, Kagefumi (Rivista di studi politici internazionali, 2013)
It is worthwhile to question whether or not it is justifiable for Asians to give higher priority to their diplomatic relations with the Holy See (hereinafter referred to as the Vatican), while the sense of distance, in particular religious distance, between Asia and the Vatican is unlikely to be shortened in the near future. My answer to this is: «Yes, it is justifiable», due to the four factors which keep the Vatican’s international stature significant, which would justify even non-Christian countries to place their diplomats in Rome. At the same time, the elevated international stature of many Asian countries is also the reality of today, which the Vatican seems to have a bit overlooked so far. The Vatican can make a deeper approach, thereby engendering more interest among Asians towards the Vatican. Without having more substantial relations with Asia, it cannot be truly universal.Il vaut la peine de se poser la question si les Asiatiques devraient donner une plus haute priorité à leur relation diplomatiques avec le Saint Siège (ci-après Vatican) ou pas, étant donné que le sens d’une distance, distance réligieuse en particulier, entre l’Asie et le Vatican ne semble pas destiné à s’amoindrir. Ma répouse est «Oui», car le stature internationale du Vatican justifie la présence diplomatique à Rome même de pays qui ne sont pas chrétiens. Aussi bien que la stature internationale, aujourd’hui élevée, de plusieurs pays Asiatiques, que le Vatican semble ne pas avoir assez remarquée jusqu’à maintenant. Le Vatican pourrait faire des démarches suivies et engendrer par cela plus d’intérêt à son égard parmi les Asiatiques. Si le Vatican aura pas plus de relations régulières en Asie, il ne pourra pas être véritablement universel.KEY-WORDS: Vatican; Non-Christian countries; Religious distance; Vatican diplomacy; International stature and diplomatic relations.